Light and electron microscopic analyses of the high deformability of adhesive toe pads in White's tree frog, Litoria caerulea. (23rd August 2016) - Nakano, Masato; Saino, Tomoyuki
ABSTRACT: White's tree frog ( Litoria caerulea ) has large, adhesive toe pads that are among the softest of all known biological structures. To explore the morphological basis for the physical properties of the toe pads, the internal microstructure of the toe pads in L. caerulea was examined using both light and transmission electron microscopy. Three design elements that are distinct from other areas of skin were observed. First, the keratinocytes comprising the adhesive surface of the toe pad all contained keratin filament bundles (tonofibrils) exhibiting structural anisotropy. Specifically, the curved conformation of the hierarchical (branching) tonofibrils was characterized by the formation of anastomoses consisting of tonofibrils beneath the adhesive cell surface and stem keratin filament bundles concentrated in the lower‐middle part of the dorsal‐side of adhesive cells. Second, the cytoplasm of keratinocytes in the most superficial cell layer contained glycoproteins (stained by periodic acid/Schiff reagent) that are considered to confer high viscoelasticity. Third, the dermis contained large lymph spaces interspersed with elastic fibers and collagen fibers, which were relatively sparsely distributed compared to the dorsal skin of the toe pads. The profiles of these structures were easily deformed by the slight application of pressure. These findings reaffirmed that the unique internal architecture of the toe pads in L. caerulea contributed to their remarkable softness and high deformability, which in turn increased the contact area and provided improved adaptability to the local topography of natural surfaces. J. Morphol. 277:1509–1516, 2016. © 2016 Wiley Periodicals, Inc.